Alterations in skeletal muscle health and biomechanical properties in patients with early rheumatoid arthritis: an exploratory cross-sectional study - Andonian, Brian J.; Patel, Hailee; Xu, Mingzhi; Sudnick, Alyssa M.; Johnson, Johanna L.; Kraus, William E.; Truskey, George A.; Huffman, Kim M. (Frontiers in Physiology, 2025)
BackgroundSkeletal muscle disease in patients with early-stage rheumatoid arthritis (RA) is understudied. The objective of this study was to identify whether patients with early RA (symptoms <6 months) have impaired skeletal muscle health.MethodsParticipants with early RA (n = 10) and age-, sex-, and BMI-matched healthy controls (n = 10) underwent cross-sectional clinical, physiological, and muscle biomechanical property assessments. Upper and lower extremity muscles underwent in vivo passive biomechanical property—tone, stiffness, and elasticity—assessments via myotonometry (MyotonPro®). In vitro muscle force production and stiffness were assessed using 3D bioengineered myobundles derived from myoblasts obtained from vastus lateralis muscle biopsies.ResultsDespite similar muscle mass and self-reported physical activity behaviors for patients with early RA and healthy controls, patients with early RA had poorer self-reported physical function, self-reported physical health, and right-hand grip strength (p < 0.05 for all). Early RA muscle tone and stiffness were lower than in controls (p < 0.05) and had an inverse association with prednisone use (rho = −0.72, p = 0.02). While 3D bioengineered myobundle force production and passive stiffness were similar to controls, early RA myobundle stiffness correlated with swollen joint count (rho = −0.67, p = 0.04).ConclusionIn this exploratory study, patients with early RA exhibited multiple skeletal muscle deficits across clinical, physiologic, and biomechanical domains compared to controls with similar muscle mass and physical activity. In vivo and in vitro skeletal muscle biomechanical assessments may be useful to identify these deficits to better understand and improve RA muscle health.